Grammatical Strategies of Persuasion in President Prabowo Subianto's D-8 Summit 2024 Speech - Herawati, Nanik; Putut Setiyadi, Dwi Bambang; Hersulastuti, Hersulastuti; Haryono, Purwo; Widiyanti, Sukasih Ratna (Universitas Pendidikan Mandalika, 2025)
A leader's speech in an international forum functions as a strategic rhetorical instrument to convey vision, foster solidarity, and assert diplomatic presence. This study analyzes the speech delivered by President Prabowo Subianto at the 2024 D-8 Summit, which centered on the call for unity among Muslim nations. Using a qualitative discourse analysis approach, the study applies Aristotelian rhetorical appeals: ethos, pathos, and logos, within a lexicogrammatical framework. The dataset comprised 37 clauses, examined through mood types, speech functions, and polarity. The findings reveal that declarative mood was dominant (62%), establishing ethos through the delivery of credible statements and objective facts. A Pathos was conveyed via both declarative and imperative moods, reflecting emotional intensity through critical remarks, expressions of solidarity, and direct appeals. Logos was constructed through the inclusion of statistical data and historical references, supporting argumentative coherence. The consistent use of inclusive pronouns such as